The Potential Capability Of Melatonin To Anticipate Postorthodontic Treatment Relapse: A Literature Review - Adya Pramusita, - (DR. P. R. YADAV, 2020)
The long-term stability outcome is the main goal of orthodontic treatment. Retainers are the most commonly used appliances to prevent orthodontic relapse. However, they are not always sufficient to manage post-orthodontic treatment relapse. An effective approach is required to anticipate the occurrence of orthodontic relapse. This review was aimed to discuss the potential use of melatonin to modulate post-orthodontic treatment relapse. Melatonin may become a promising agent to regulate orthodontic relapse, through modulating alveolar bone remodeling by stimulating osteoblast and inhibiting osteoclast. Administration of melatonin in rodents model promotes bone mass, bone formation, impairs bone healing and inhibits bone loss. In addition, nightly melatonin supplementation in perimenopausal women is well tolerated and may improve the imbalance in bone remodeling. Melatonin also accelerates osteogenic differentiation in various cell cultures through melatonin 2 receptor (MT2R) by activating multiple signal cascade including MEK1/2 and 5, Wnt 5 a/b, BMP-2 and -4, PDGF/AKT signaling pathway. Furthermore, melatonin has also been reported to suppress osteoclastogenesis directly through melatonin 1 receptor (MT1R)/MT2R by inhibiting NF-kB signaling pathway and indirectly by decreasing RANKL/OPG ratio from osteoblast. Thus, melatonin may provide a new direction in controlling post-orthodontic relapse, by stimulating bone formation and inhibiting bone resorption.